An analysis of a criterion-referenced test in elementary mathematics - Garcia, Perla T. (1977)
This study was undertaken to analyze one of the criterion-referenced tests in elementary mathematics constructed by a team of teachers in the Grade School Department of St. Scholastica's College, Manila. It attempted to apply some new approaches in determining the adequacy of the test items. Among the methods and techniques used were the McNemar test for significance, and the Biserial r statistical technique.